The Importance of CLT (Communicative Language Teaching) Method in Teaching Different Age Groups of Students - Kiyamiddinovna, Umarova Malika (International Journal on Human-Computing Studies, 2023)
Communicative Language Teaching (CLT) has become one of the most common methods in classrooms around the world with students of all ages and at all levels of ability. It is generally believed that the goal of English language learning is to develop communication skills, and to accomplish this communicative approaches to language teaching are widely advocated. However, it is not clear whether approaches to communicative language teaching (CLT) used for adult learners are suitable for younger learners of English. Therefore, this article seeks to critically examine communicative language teaching with the intent to identify appropriate classroom practice for different age groups of learners.